The impact of QRIS implementation on the growth and competitiveness of small tourism businesses in Bali - Kencanawati, Anak Agung Ayu Mirah; Jaya, I Made Sura Ambara; Masih, Ni Ketut; Supiatni, Ni Nyoman (Journal of Commerce, Management, and Tourism Studies, 2025)
The implementation of the Quick Response Code Indonesian Standard (QRIS) has emerged as a pivotal development in the digital transformation of Indonesia’s payment systems. In Bali, a region heavily dependent on tourism, the adoption of QRIS has significant implications for the growth and competitiveness of small tourism-related businesses. This study investigates the extent to which QRIS has contributed to enhancing operational efficiency, market accessibility, and financial inclusion among micro, small, and medium enterprises (MSMEs) in the tourism sector. Using a mixed-methods approach combining quantitative survey data and qualitative interviews with small business owners in key tourist destinations such as Ubud, Seminyak, and Nusa Penida, this research identifies key drivers and challenges associated with QRIS usage. Findings indicate that QRIS adoption has reduced transaction costs, improved customer convenience, and enhanced business visibility among domestic and international tourists. Moreover, QRIS facilitates better financial record-keeping, which is instrumental in accessing microcredit and other forms of institutional support. Despite its benefits, challenges persist, particularly related to digital literacy, infrastructure availability, and inconsistent regulatory enforcement. The study concludes that while QRIS significantly boosts competitiveness and resilience among small tourism enterprises, its optimal impact depends on sustained digital education, government incentives, and inclusive policy frameworks. This paper contributes to the growing body of literature on digital payment systems and MSME development in emerging economies. It offers actionable recommendations for policymakers, financial institutions, and tourism stakeholders aiming to maximize the socioeconomic impact of QRIS in Indonesia and beyond.